Axillary reverse mapping in patients with breast cancer: Is it oncologically safe?. Issue 7 (4th April 2016) - Ngui, Nicholas K.; French, James; Kilby, Christopher J.; Pathmanathan, Nirmala; Elder, Elisabeth E.
Abstract : Background: Axillary reverse mapping (ARM) is a technique used to identify the lymphatics draining the arm. The aim of this study was to examine the prevalence and predictors of ARM node metastases in breast cancer patients undergoing an axillary lymph node dissection (ALND). Methods: A total of 87 patients were enrolled in this study. Patent V Blue dye was injected in the upper arm for ARM node localization. All patients had an ALND with the identified ARM node removed and sent separately for histologic analysis. Results: Of 67 (77%) patients in whom an ARM node was identified, 49 (73%) were negative and 18 (27%) were positive for metastases on final histopathology. Positive ARM node status was significantly associated with advanced axillary disease, and larger primary cancers. Patients requiring a completion ALND due to a positive sentinel lymph node biopsy (SLNB) with non‐suspicious ARM nodes during surgery did not have ARM node metastases. Conclusions: There is a high risk of ARM node involvement, approximately a quarter, in patients with preoperatively known lymph node metastases from breast cancer. However, it may be safe to preserve a clinically non‐suspicious ARM node in patients with a positive SLNB who require a completion ALND. J. Surg. Oncol. 2016;113:726–731 . © 2016 Wiley Periodicals, Inc.